Service Innovation in Developing Economies : Evidence from Latin America and the Caribbean - Rubalcaba, Luis; Aboal, Diego; Garda, Paula (Taylor and Francis, 2016)
This paper proposes a framework for understanding key aspects of service innovation in developing economies, based on four dimensions: first, the integration of services in national innovation systems; second, competences and preferences; third, networking and cooperation; and, fourth, outcomes in terms of socio-economic impacts. This conceptual framework is matched with new evidence from case studies performed in six different Latin America and the Caribbean countries (Argentina, Chile, Brazil, Uruguay, Costa Rica and Jamaica) and nine sectors (tourism, software-ICT, outsourcing, mining, logistics, retail, creative services, sport services and biotech services). The results reveal the importance of specificities in service innovation and suggest policy and managerial implications.